Heart rate variability and perinatal depressive symptoms: A scoping review protocol - Claudio Singh Solorzano; Marta Spinoni; Maria Grazia Di Benedetto; Alessandra Biaggi; Moira Marizzoni; Elena Gatti; Cristina Festari; Michela Pievani; Caterina Grano; Annamaria Cattaneo (Brain, Behavior, & Immunity - Health)
Objective: An emerging marker of depression in the perinatal period is represented by a reduction in the autonomic nervous system (ANS) activity, reflected by heart rate variability (HRV). This scoping review aims to map the association between HRV and depression during the perinatal period and to understand its potential clinical implications. Introduction: Previous evidence associated ANS dysfunction and depressive symptomatology in the general population. Few observational and intervention studies investigated how HRV could be related to both pre- and post-partum depressive symptoms. However, high heterogeneity in the study designs and methods has been reported. Therefore, this scoping review plans to combine all these findings to build a starting point for future research. Inclusion criteria: This scoping review will consider articles focusing on the association between HRV and depression in the peripartum and – when available – on the impact of interventions on HRV and how this correlates with changes in depressive symptoms. Studies will be included with no restrictions on participants’ age, peripartum time points for the assessment, and HRV parameters collected. Methods: We will perform a systematic search using the Medline (PubMed), PsychInfo, and Web of Science (WoS) databases. Two authors will independently screen titles, abstracts, and then full-text articles that meet the inclusion criteria. The review will include only journal articles published in English, with no time limitations. Data will be extracted and presented in tables and/or graphical representations to summarise and describe the results. Extracted data will be reported in a comprehensive summary.